Epidemiology and risk factors for endoparasite infection in subtropical feral cattle in Hong Kong - Tania A. Perroux; Samantha S.Y. Lie; Alan G. McElligott; Danchen A. Yang; Fraser I. Hill; George M.W. Hodgson; Wing S. Wong; Kate J. Flay (International Journal for Parasitology: Parasites and Wildlife)
Understanding parasite epidemiology is essential for managing endoparasite infections in free-ranging animals. However, such epidemiological knowledge is limited for feral cattle and is usually derived from farmed populations. We assessed endoparasite infection in a feral cattle population in Hong Kong. This population does not receive any routine care or anthelminthic treatment, although some cattle are provisioned with water and hay by local citizens. We assessed three indices of endoparasite infection (parasite richness, prevalence and fecal egg/oocyst count) and their associated risk factors (season, provisioning, marshland access, group size, sex and body condition) in adult cattle.We conducted sedimentation, McMaster and coproculture techniques on 262 samples collected from 177 cattle. We identified eleven taxa of nematodes, two taxa of trematodes, one taxon of protozoan and one taxon of cestode. Median parasite richness was two parasite taxa per individual. Trematode infections were the most prevalent (91.22 %), followed by protozoan (67.17 %), nematode (23.22 %) and cestode (12.97 %) infections. Counts averaged 144.85 oocysts per gram for Eimeria oocysts, 20.61 eggs per gram (EPG) for strongyle-type eggs, 11.83 EPG for Moniezia and 1.91 EPG for Trichuris. Provisioned herds were more likely to be infected with Eimeria, but had lower prevalence of Trichostrongylus. Eimeria prevalence and strongyle-type egg counts were higher in the wet season, while Fasciola eggs, Cooperia and Trichostrongylus larvae were more prevalent in the dry season. Larger herds had higher Eimeria oocyst prevalence but lower Fasciola egg prevalence. Marshland access decreased Fasciola egg prevalence while it increased prevalence of Cooperia larvae. Males were more infected with strongyle-type eggs than female cattle.We show that the seasonal dynamics of infection and consequences of provisioning differ between endoparasite taxa. Our findings highlight complex interactions between endoparasites and their hosts, providing new insights into wild ruminants’ health and the impacts of anthropogenic provisioning.